MAN AND LOGOS: HERACLITUS’ SECRET - A. V. Halapsis (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The author believes that the main topic of philosophical studies of Heraclitus was not nature, not dialectics, and not political philosophy; he was engaged in the development of philosophical anthropology, and all other questions raised by him were subordinated to it to one degree or another. It is anthropology that is the most "dark" part of the teachings of this philosopher, therefore the purpose of this article is to identify the hidden anthropological message of Heraclitus. In case of success, it will become clear what made him "darken". Theoretical basis. The methodological basis of the article is the anthropological understanding of fragments of Heraclitus’ texts presented in a historical and philosophical context. Originality. The philosophical concept of Heraclitus is still a mystery for researchers of his work. The author of the article proposed such a variant of interpretation, within the framework of which different elements of this concept fit into a consistent model. Conclusions. The article proves that although the anthropological turn in philosophy is traditionally associated with the activities of the sophists and Socrates, the previous philosophical thought was also not devoid of anthropological ideas. Moreover, pre-Socratic philosophers posed problems, the interpretation of which brought the doctrine of man to the level of high-order abstractions, while surprisingly preserving the concreteness of the life-meaning questions that confront him. And one of the brightest representatives of pre-Socratic anthropology was Heraclitus of Ephesus. Religion was the motivator that made him study the world, man, and society. The doctrine of the Logos developed by Heraclitus had a tremendous impact on Plato and Philo of Alexandria, and through them on the author of the Fourth Gospel, who begins his story with a "Greek" rethinking of the mystery of the Incarnation. If Heraclitus claimed that a person carries a particle of the Logos, then John (or the one who wrote on his behalf) proclaimed that the Logos itself incorporated a particle of man. Despite all the differences between these approaches, each of them postulated the cosmic (divine) significance of human existence, which means that it brought anthropology to the ontological level.